Influência das armaduras longitudinais inferiores e superiores na resistência à força cortante em lajes maciças - Costa, Mayuma de Oliveira Peres (2022)
Among the elements that composes a strucuture, we have the surface elements, which are the ones the thickness is smaller than the other dimensions. Slabs are examples of these elements. Amid the many efforts it must resist, there is the shear force, which generates shear stress. In some components, this stress is hold up by uncracked concrete and reinforcements. In some cases, the components do not have reinforcements to resist the shear force and then the stress must be beared through other factors. Some of the factors that influence the resistance to this shear stress are thickness, longitudinal reinforcement, concrete compressive strength, crack size, and others. The present paper analyzes, experimentally, what is the influence in the variation in the height of the pieces (8, 11 e 14 cm) and in the reinforcement in the shear strength. For this, 9 slabs were studied, varied according to the parameters mentioned above. Regarding the height variation, it is concluded that the increase in height, even with the same reinforcement rates, contributed to the increase of the ultimate resistant force. Maintaining the height, increasing the reinforcement ratio, with the inclusion of superior reinforcement, also resulted in an increase in the ultimate strength of the part. Analyzing the displacements, it was noticed that, for the slab with the highest height, the part was the most rigid.